Composition, Identity and Cardinality [Composición, Identidad y Cardinalidad] - Briceno-Dominguez, J (Universidad De Valparaíso, Chile, 2020)
In this article I attempt to give an account of the thesis according to which composition is identity and of the criticisms that might be formulated against it. According to a weak version of the thesis, composition, in virtue of being analogous in important respects to identity, is as ontologically innocent as identity. According to the strong version of the thesis, composition is literally a species of the generic relation of identity, and is as ontologically innocent as any species of identity. As we will see, the weak version begs the question or incurs in a non sequitur; and the strong version is incoherent and faces a dilemma. Thus, composition is not identity: One thing cannot be identical to many things. © 2020 University of Valparaiso. All rights reserved.